Intravenous fentanyl vs. topical lignocaine for ProSeal™ laryngeal mask airway insertion with propofol induction - Rahmat Ameen Noorazyze, Nurzohara Aisha Noorazyze; Nor, Nadia Md; Zain, Jaafar Md; Mohamad Yusof, Aliza; Yong, Liu Chian (Frontiers in Medicine, 2022)
Insertion of the laryngeal mask airway (LMA) without muscle relaxant requires adequate obtundation of airway reflexes, which may otherwise lead to incorrect or failed LMA placement. This study compared topical lignocaine spray versus intravenous (IV) fentanyl, during propofol induction for insertion of the ProSealTM LMA (PLMA). This was a prospective, randomized, double blind study, in ASA I or II patients, for elective or emergency surgery. Seventy patients (n=70) who fulfilled the inclusion criteria were randomly assigned to receive IV fentanyl 2mcg/kg or topical lignocaine spray 40mg, prior to anaesthesia induction with IV propofol (2-2.5mg/kg). ProSealTM LMA insertion condition was regarded optimal in the absence of adverse responses (gag, cough, laryngospasm and body movements), and successful LMA placement at the first attempt. Haemodynamic parameters were recorded and patients were assessed for sore throat and hoarseness post operatively. Seventy patients were analysed. The number of patients with optimal PLMA insertion conditions were comparable between the groups (60% vs 57%, P=0.808). All haemodynamic parameters were comparable between groups with the exception of heart rate (HR). Sympathetic obtundation of heart rate was greater with IV fentanyl than topical lignocaine (P<0.05). The proportion of patients with postoperative sore throat significantly increased with the number of insertion attempts (P<0.05). Topical lignocaine spray to the pharynx is as effective, and may be an alternative to IV fentanyl, during propofol induction for PLMA insertion. Success rate and optimal insertion condition at the first attempt, propofol requirement, blood pressure, adverse events and airway complications were comparable. Heart rate obtundation was less with topical lignocaine spray but remained within clinically acceptable values.